The Environment in the Age of the Internet Activists, Communication, and the Digital Landscape - Graf, Heike (Open Book Publishers, 2016)
"How do we talk about the environment? Does this communication reveal and construct meaning? Is the environment expressed and foregrounded in the new landscape of digital media? The Environment in the Age of the Internet is an interdisciplinary collection that draws together research and answers from media and communication studies, social sciences, modern history, and folklore studies. Edited by Heike Graf, its focus is on the communicative approaches taken by different groups to ecological issues, shedding light on how these groups tell their distinctive stories of ""the environment"". This book draws on case studies from around the world and focuses on activists of radically different kinds: protestors against pulp mills in South America, resistance to mining in the Sámi region of Sweden, the struggles of indigenous peoples from the Arctic to the Amazon, gardening bloggers in northern Europe, and neo-Nazi environmentalists in Germany. Each case is examined in relation to its multifaceted media coverage, mainstream and digital, professional and amateur. Stories are told within a context; examining the ""what"" and ""how"" of these environmental stories demonstrates how contexts determine communication, and how communication raises and shapes awareness. These issues have never been more urgent, this work never more timely. The Environment in the Age of the Internet is essential reading for everyone interested in how humans relate to their environment in the digital age."